Immunometabolism in cancer: a systemic perspective - Moretti, Helena; Cioccoloni, Giorgia; Perucha, Esperanza (Frontiers in Immunology, 2025)
Cancer incidence is increasing, becoming a significant public health concern. Cancer arises from the uncontrolled division of cells that cannot be restrained by the anti-tumour response mounted by the immune system. Both tumour and immune cells require high levels of energy in the form of ATP and synthesis of macromolecules to support differentiation and proliferation. To support these metabolic demands, adaptations at the cell, tissue and systemic level are required. Here, we take a systemic perspective to summarise the energetic needs of the anti-tumour response and how metabolic overload and obesity affects these processes. We describe how immunotherapies that aim to reverse immune cell exhaustion have unexpected effects depending on the metabolic background of the patient and finally we propose the use of this knowledge to advance current cancer prevention and treatment strategies.